2014
DOI: 10.1097/scs.0b013e3182a21056
|View full text |Cite
|
Sign up to set email alerts
|

Early Pressure Dressing for the Prevention of Subdural Effusion Secondary to Decompressive Craniectomy in Patients With Severe Traumatic Brain Injury

Abstract: This study was performed to investigate the effect of early pressure dressing on the prevention of postoperative subdural effusion secondary to decompressive craniectomy (DC) in patients with severe traumatic brain injury (STBI). Patients with STBI who had undergone DC for refractory increased intracranial pressure between January 2008 and December 2011 (n = 169) were randomly divided into early pressure dressing (n = 82) and control (n = 87) groups. Early pressure dressing with an elastic bandage or general w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Early pressure dressing applied 7–10 days after DC has been shown to reduce this complication in a small randomized controlled trial ( 43 ). A tense collection of fluid can rarely cause pressure on the brain due to a ball valve effect and has been termed external brain tamponade and such hygromas require drainage ( 16 , 44 , 45 ).…”
Section: Early Complicationsmentioning
confidence: 99%
“…Early pressure dressing applied 7–10 days after DC has been shown to reduce this complication in a small randomized controlled trial ( 43 ). A tense collection of fluid can rarely cause pressure on the brain due to a ball valve effect and has been termed external brain tamponade and such hygromas require drainage ( 16 , 44 , 45 ).…”
Section: Early Complicationsmentioning
confidence: 99%
“…The placement of a pressure dressing in the immediate postoperative period is associated with decreased rate of subdural effusion in the traumatic brain injury population. 11 However, this finding needs to be studied in the patient population with stroke.…”
Section: Livesay and Mosermentioning
confidence: 99%
“…A total of 1844 abstracts were excluded due to the following reasons: no study on TBI ( n = 785), no RCT ( n = 431), laboratory study ( n = 88), delayed intervention (e.g., study on rehabilitation techniques; n = 300), no original article ( n = 222), other reasons ( n = 18).During the further analysis of the 82 studies left, five studies had to be excluded, as the full-text revealed that the studies did not meet the criteria of RCTs; two more articles had to be excluded as the full-texts were only available in Russian/Chinese; three articles were identified as review articles. Therefore, a total of 72 articles [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58...…”
Section: Resultsmentioning
confidence: 99%